Mycobacterium tuberculosis Biology Revealed by Proteome Profiling and Integration of Multi-omics Data—Proteomics Insight into M. tuberculosis Systems Biology - Deng, Wanyan; Fan, Xiangyu; Wang, Xiaozhen; He, Ying; Li, Zihui; Song, Jie; Ping, Lingyan; Chang, Lei; Minh Duong, Duc; Zhang, Zongde; Xu, Ping; Xie, Jianping (Current Proteomics, 2013)
Mycobacterium tuberculosis is the causative agent of tuberculosis, an old formidable scourge of global public health. Despite decades of intensive studies on the biology and physiology of M.tuberculosis, the function of about one-quarter open reading frame (ORF) of the M.tuberculosis genome remains elusive. In order to determine the size of M.tuberculosis proteome during normal in vitro growth, shotgun proteomic profiling and cross-reference to available multi-omics data were performed. We identified 2817 M.tuberculosis ORFs, about 70% of the predicted encoding capacity. More interestingly, 228 novel proteins which had not been predicted by the 1998 genomic annotation were found. These novel proteins participated in various cellular events including intracellular growth, persistence and dormancy. The proteins with potential value in diagnostic biomarker, drug target and host immune response targets were thoroughly aligned with available transcriptional data. One unexpected discovery is the absence of the key components involved in the base-excision repair pathway which was crucial for M.tuberculosis survival. These data provided fresh insights into the biology of this old pathogen.
Keywords: Proteome